2023
DOI: 10.1128/spectrum.03617-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Evolutionary Insights into Australian Toxigenic Vibrio cholerae O1 Strains

Abstract: Australia has its own indigenous V. cholerae strains, both toxigenic and nontoxigenic, that are associated with disease. Exotic strains are also detected in Australian patients returning from overseas travel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…In a similar way, genotype 2 ctxB -containing CTX prophage was previously reported in outbreak-related V. cholerae O1 El Tor strains from Australia ( 34 ) and is also observed in clinical NOVC strains in this study. Notably, three of the toxigenic NOVC clinical and environmental strains, M12590, M138351, and 243712, had single or double copies of the genotype 2-containing CTX phage region as shown in Table 2 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In a similar way, genotype 2 ctxB -containing CTX prophage was previously reported in outbreak-related V. cholerae O1 El Tor strains from Australia ( 34 ) and is also observed in clinical NOVC strains in this study. Notably, three of the toxigenic NOVC clinical and environmental strains, M12590, M138351, and 243712, had single or double copies of the genotype 2-containing CTX phage region as shown in Table 2 .…”
Section: Discussionsupporting
confidence: 89%
“…This study has extensively investigated the genotypic features of clinical and environmental NOVC strains from Australia as having similar virulence potential. Interestingly, in this study we confirmed the presence of ctxB genotype 2, CTX phage region, among environmental NOVC strains from Australia similar to toxigenic Queensland outbreak-related O1 El Tor V. cholerae clinical and environmental strains from our previous study ( 34 ). Thus, based on our characterization of these strains QLD waterways harbor genetically diverse V. cholerae strains, which may be due to the mechanism of horizontal gene transfer and the bipartite architecture of V. cholerae ’s genome.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations